Evaluation of interdisciplinary care pathway implementation in older elective surgery patients. Issue 4 (27th January 2023) - Hu, Frances Y.; Rowe, Katherine A.; O'Mara, Lynne M.; Bulger, Amy; Bleday, Ronald; Groff, Michael W.; Cooper, Zara; Bernacki, Rachelle E.
Abstract: Background: The American College of Surgeons Geriatric Surgery Verification Program outlines best practices for surgical care in older adults. These recommendations have guided institutions to create workflows to better support needs specific to older surgical patients. This qualitative study explored clinician experiences to understand influences on implementation of frailty screening and an interdisciplinary care pathway in older elective colorectal surgery and neurosurgery patients. Study Design: Semi‐structured in‐person and video‐based interviews were conducted from July 2021 to March 2022 with clinicians caring for patients ≥70 years on the colorectal surgery and neurosurgery services. Interviews addressed familiarity with and beliefs about the intervention, intervention alignment with routine workflow and workflow adaptations, and barriers and facilitators to performing the intervention. Interviews were analyzed using the consolidated framework for implementation research (CFIR) to find themes related to ongoing implementation. Results: Thirty‐two clinicians participated (56.3% female, 58.8% White). Fifteen relevant CFIR constructs were identified. Key themes to implementation success included strong participant belief in effectiveness of the intervention and its advantage over standard care; the importance of training, reference materials, and champions; and the need for institution‐level investment in resources to amplify the impact of the intervention on patients and expand the capacity to address their needs. Conclusion: Systematic evaluation found implementation of frailty screening and an interdisciplinary care pathway in elective colorectal surgery and neurosurgery patients to be supported by participating clinicians, yet sustainability of the intervention and further adoption across surgical services to better meet the needs of older patients would necessitate organizational resource allocation.